Acquisition of Vallent by IBM: An insight into the Change Management Model and its feasibility in Cross Nation Scenario - Fatehpuria, Nidhi (2008)
One of the biggest challenge facing today’s organizations involves change management as the ultra-competitive market place requires leaders to often try to alter the way they do business. To successfully transform the organizations to meet their goals would entail strong leadership to bring about the change together with employees that understand and are motivated to undergo the change. In this research, my objective is to investigate specifically the change management at IBM after the acquisition of Vallent and deduce a conclusion regarding the viability of this change model exactly as is in a cross nation scenario, particularly India. The focus of this study is IBM since IBM has undergone the change recently and is the most talked about case study. This study employs a case study approach to discuss the change models adopted by the organization through the use of in-depth interviews to create understanding of the interaction between the change agent and the employees. The findings of the study reveal that there has been only little similarity between the actual models adopted and the academic models. Also the study suggests that imitating and copying models as it is from one country to another may be dangerous in various grounds and may damage the psychological contract of the employees. These outcomes suggest that organization and its management should adopt a holistic view when approaching change management; taking in consideration factors affecting employees’ motivation and the form of leadership needed to make it successful.